2016
DOI: 10.1371/journal.pone.0166813
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Analysis of Serum Autoantibody-Reactivities in Patients with Primary Open Angle Glaucoma and Optic Disc Hemorrhage

Abstract: BackgroundThe aim of our current investigation was to analyze the autoantibody-reactivities of primary open angle glaucoma patients with optic disc hemorrhage as possibly correlated to disease progression by means of a protein microarray approach.MethodsSera of patients with primary open angle glaucoma and optic disc hemorrhage (n = 16) were collected directly after study inclusion (0 weeks) and after 2 weeks, 4 weeks and 12 weeks. As a control group patients with primary open angle glaucoma (n = 18) were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 57 publications
1
2
0
Order By: Relevance
“…In line with these results, a longitudinal study revealed a gradual increment of serum autoantibodies in glaucoma patients with optic disc hemorrhages and no detectable change in patients with no optic disc hemorrhages [217]. In addition, the transfer of mononuclear cells from patients with optic disc hemorrhages into immune-deficient mice resulted in increased RGC loss [145,217]. e tracing of circulating monocytes with an inflammatory profile in the DBA/2J model confirmed the entry of these cells into the ONH and its contribution to glaucomatous damage [17].…”
Section: Leukocyte Infiltrationsupporting
confidence: 72%
See 1 more Smart Citation
“…In line with these results, a longitudinal study revealed a gradual increment of serum autoantibodies in glaucoma patients with optic disc hemorrhages and no detectable change in patients with no optic disc hemorrhages [217]. In addition, the transfer of mononuclear cells from patients with optic disc hemorrhages into immune-deficient mice resulted in increased RGC loss [145,217]. e tracing of circulating monocytes with an inflammatory profile in the DBA/2J model confirmed the entry of these cells into the ONH and its contribution to glaucomatous damage [17].…”
Section: Leukocyte Infiltrationsupporting
confidence: 72%
“…Breaches in the blood-retina barrier may become visible and result in small optic disc hemorrhages or parapapillary chorioretinal atrophy areas, both of which are commonly detectable in glaucomatous eyes [ 215 , 216 ]. In line with these results, a longitudinal study revealed a gradual increment of serum autoantibodies in glaucoma patients with optic disc hemorrhages and no detectable change in patients with no optic disc hemorrhages [ 217 ]. In addition, the transfer of mononuclear cells from patients with optic disc hemorrhages into immune-deficient mice resulted in increased RGC loss [ 145 , 217 ].…”
Section: Activation Of the Immune Systemmentioning
confidence: 56%
“…Interestingly, activated microglia have been found strategically positioned within the regions of parapapillary chorioretinal atrophy in glaucomatous eyes [26,27]. A longitudinal study of serum autoantibody reactivity has also showed an increase over time in glaucoma patients with optic disc hemorrhages, but no change has been detected in patients without optic disc hemorrhages [97]. Consistent with these observations, transfer of the mononuclear cells obtained from glaucoma patients with optic disc hemorrhages into immune deficient mice has resulted in a marked decrease in RGC density (presented at the Annual Meeting of the Association for Research in Vision and Ophthalmology, 2018, Abstract # 3731).…”
Section: Systemic Immune Responsesmentioning
confidence: 99%